The War Vascular Injuries - أحمد, غانم (Latakia University Journal -Medical Sciences Series, 2021)
The incidence of vascular injuries resulting from war injuries has increased in Syria due to the conditions of war. It was previously considered rare and rare for a long time, This constituted a great challenge to vascular surgeons in particular, and surgeons in general, because of the seriousness of these injuries, whether the risk of vascular damage or the risk of accompanying injuries such as bone fractures or nerve injuries; etc. This may led to a disastrous results such as; partial or total limb amputation, or limb incompetence. These kinds of injuries were considered a real medical conditions, cause for several reasons, including: the lack of medical Experiences and medical staffs in this particular field, as well as the lack of diagnostic and treatment methods, and their high costs due to the conditions of war.